Stress, Anxiety, and Depression in Dentistry Students: The Impact of the COVID-19 Pandemic and Sociodemographic Factors - Gustavo Correia Basto da Silva; Geanderson José Marques Barbosa; Mayara Cabral de Brito Santiago; Ítalo Cardoso dos Santos; Ricardo Alves de Olinda (Association of Support to Oral Health Research (APESB), 2024)
Objective: To assess the influence of the COVID-19 pandemic and sociodemographic factors on stress, anxiety, and depression levels among dental students. Material and Methods: This observational study employed a census approach featuring a quantitative, descriptive, and analytical cross-sectional analysis. The research was conducted within a university center in northeastern Brazil from March to May 2021. Two questionnaires were administered: the Depression, Anxiety, and Stress Scale (DASS-21) and another survey focusing on sociodemographic factors. Pearson's chi-square test was employed to examine potential associations between the variables, and multiple logistic regression models were fitted, with a significance level set at 5%. Results: The study included 128 dentistry students, predominantly female, with a high monthly family income. The data revealed normal levels across the three DASS subscales. A significant association was observed between anxiety and sex (X2=10.37; p=0.03). The depression subscale exhibited associations with ethnic group (X2=47.46; p<0.01), area of residence (X2=12.44; p=0.03), and appropriate study space (X2=11.48; p=0.04). Urban residents were 4.29 times more likely to experience depression than their rural counterparts (OR=4.29; 95%CI 1.28-14.42). Conclusion: While psychological profiles were as expected, targeted interventions for vulnerable groups are crucial. Future research should use longitudinal designs and assess tailored interventions' effectiveness to enhance mental health outcomes among students.